The grateful eight: perspectives on higher education affordances and tensions and didactics role in enhancing learning experiences towards sustainability - Nordén, Birgitta; Ulvenblad, Pia; Mäenpää, Antti; Vogopoulou, Areti; Dourado, Alcina; Merkisz-Guranowska, Agnieszka; Lundberg, Anna L. V.; Schiöth, Helgi B. (Frontiers media, 2026)
Sustainability actions have the potential to exert a lasting impact on higher education didactics. Universities are often regarded as key actors in educating the next generation of decision-makers who are capable of making more informed choices from a sustainability perspective. However, significant challenges remain regarding the understanding about how sustainability can be integrated into higher education, and disciplines differ considerably in how they engage with the topic. To address these issues, we employ collaborative auto-ethnographic approach to examine how eight lecturers from different disciplinary backgrounds approached sustainability education, and what affordances and tensions they encountered during and after a joint international course on Higher Education Didactics for Sustainability organized by Karlstad University in Sweden. The findings indicate that substantial challenges persist, despite participants’ high levels of motivation and transdisciplinary mindsets. These challenges appear to be linked to disciplinary differences in approaches and emphasis regarding which aspects of sustainability education are considered applicable to the participants’ teaching practices.
Keywords: sustainability; education; autoethnography; affordances; didactics; HEDS; higher education; STEM; tensions; transdisciplinary teaching approaches; fi=Aluetiede|en=Regional Studies|